Digitalization as an Imperative of the Development of Business Processes in the Conditions of the Intensified Global Competitiveness - Krylov, Denys; Pohrebniak, Anna; Pereguda, Yuliia; Stetsiuk, Viktor; Ostrovska, Natalia (REVISTA DE LA UNIVERSIDAD DEL ZULIA, 2023)
The article examines the peculiarities of the digital development on a global scale, its impact on the development of business processes in the conditions of the intensified global competitiveness. The number of Internet users in the world was analyzed, which made it possible to outline the main global trends in the development and implementation of digital technologies by country. The systematic approach in research makes it possible to identify regularities and relationships, as well as to obtain the effect of synergy by considering a set of processes and their subordination caused by external causes of influence, including competitive trends of globalization.The opportunities that arise in companies due to the involvement of digital technologies in business processes are outlined. Having singled out the threats of the introduction of digital technologies into business processes, directions for their elimination are proposed. To ensure the digitalization of business processes in the face of the intensified global competitiveness, directions for promoting digitization at the macro level have been identified.
Keywords: Digitization, digital technologies, digital transformation, business processes, competition, global competitiveness